Fossil Fuel Subsidies in the Sustainable Urban Transport Agenda: A Maqaṣid al-Shari‘ah Approach - Wempie Yuliane; Bayu Arie Fianto; Aam Slamet Rusydiana; Sulistya Rusgianto; Rheza Hermawan (Yayasan Darussalam Bengkulu, 2026)
Background: Urban transport systems in many Muslim-majority countries face persistent challenges from rapid motorization, underinvestment in public transport, and long-standing fossil fuel subsidies. Although politically popular, these subsidies distort price signals, encourage excessive private vehicle use, and contribute to congestion, air pollution, public health risks, and limited fiscal space for sustainable mobility investments. Method: This qualitative conceptual study reviewed Islamic jurisprudence, Islamic ethics, fossil fuel subsidies, transport externalities, and sustainable urban transport. It applies maqasid al-shariah, maslahah, khilafah, and la darar wa la diror to evaluate fossil fuel subsidies and sustainable urban transport from an Islamic ethical policy perspective. Results: Fossil fuel subsidies are found to generate ethical and socio-policy concerns when they encourage excessive private vehicle use, intensify negative transport externalities, and constrain public transport investment. From an Islamic ethical perspective, these effects may undermine life, wealth, public welfare, and environmental stewardship, whereas sustainable urban transport reflects harm prevention, public interest, moderation, and responsible stewardship better. Research limitations: This conceptual-normative paper develops an Islamic ethical-policy framework. Future research should empirically validate it through city-level case studies, stakeholder interviews, and behavioral studies on sustainable mobility acceptance. Originality/value: This study frames sustainable urban transport as an Islamic ethical policy imperative when mobility-related harm threatens the public welfare. Its originality lies in applying maqasid al-shariah, maslahah, khilafah, and la darar wa la diror to reassess fossil fuel subsidies and support sustainable mobility transitions, thus offering an ethical basis for subsidy reform, public transport investment, and policy acceptance.